Enabling the High‐Voltage Operation of Layered Ternary Oxide Cathodes via Thermally Tailored Interphase (Small Methods 4/2022). Issue 4 (18th April 2022) - Zhu, Zhiqiang; Cao, Shengkai; Ge, Xiang; Xi, Shibo; Xia, Huarong; Zhang, Wei; Lv, Zhisheng; Wei, Jiaqi; Chen, Xiaodong
Abstract : Inside Back Cover In article number 2100920, Xiaodong Chen and co‐workers propose a novel high‐temperature pre‐cycling approach to construct in‐situ a uniform and robust cathode/electrolyte interphase on LiNi x M n yCo z O2 cathode materials, which helps to suppress parasitic interfacial reactions in subsequent cycling and thus enables Li‐ion battery operation in high voltage conditions with good cyclic stability.